Evolución de la logística internacional en la exportación de petróleo en el mercado mundial (2020)
What will be presented in this paper is an analysis of how international logistics in the export of oil in the world market has evolved, taking into account the different factors that have affected this export logistics such as the different ports of exporting countries of oil, and also the different types of storage and transportation of oil that complement the logistics in the export of oil. Based on the above, it was necessary to investigate and focus the different ports worldwide that handle the largest amount of oil, examining data in different articles from which the ports with the largest oil export worldwide could be identified, after verifying the main ports we went on to verify the different modalities of oil storage and also as the way of transporting oil has changed, the different modalities of oil transport, its advantages, disadvantages and also benefits and risks were analyzed, finally the relationship between the transport and storage of oil in the world market.